Acute toxicity and therapeutic application of Zizyphus lotus and Ruta chalepensis phenolic extracts in treatment of gastroenteritis induced by Salmonella enterica subsp. arizonae - Bekkar, Nour El Houda; Bouabsa, Foufa; Meddah, Boumediene; Keskin, Bahadir; Cakmak, Yavuz Selim; Tou, Abdenacer (Acta Biologica Szegediensis, 2023)
This study aimed to evaluate the antigastroenteritis effect against Salmonella enterica subsp. arizonae after therapeutic application of hydromethanolic extracts (MeOH.E) and aqueous extracts (Aq.E) of Zizyphus lotus (ZL) and Ruta chalepensis (RC). Acute oral toxicity was elucidated using in vivo methods and antigastroenteritis effect were evaluated using S. enterica subsp. arizonae-induced diarrheal model. Furthermore, test groups were treated with 400 mg/kg of the MeOH.E and Aq.E of each plant, while the control group was given neomycin (200 mg/kg) as standard antibiotic treatment, positive and negative controls were given the infectious germ (4 × 106 cells/mL) and 0.9% saline solution NaCl (10 ml/kg), respectively. Both plants extracts showed no toxicity for all the animals, so the LD50 was found to be greater than 5000 mg/kg. Moreover, an important bactericidal effect, using both plants extracts was determined against S. enterica subsp. arizonae cells in the intestine. In parallel, a decrease in alkaline phosphatase, amino alanine transferase and aspartate aminotransferase levels was observed with reduction in blood erythrocyte sedimentation rate in all treated animals. Thus, these results could be exploited in the medical field for the formulation of potent antibacterial drugs that cure severe gastrointestinal infections.